Pengaruh Stres pada Ibu Hamil Trimester III terhadap Aktivitas Janin yang Dikandung di Wilayah Puskesmas Grabag 1 Kabupaten Magelang - Wiwin Renny Rahmawati (Prodi Keperawatan Purwokerto, 2019)
Background. Stress experienced third trimester pregnant women may adversely affect pregnant women and fetus. According to the study, pregnant women who have high stress levels can increase the risk of preterm birth, even miscarriage. When a pregnant woman to feel anxiety and stress, the body will produce stress hormones that can affect the fetus that affects inhibit blood vessel and reduces the supply of oxygen to the fetus, and cause abnormal activity or movement. Objective. To determine the effect of stress on the third trimester pregnant women to the fetus activity in the health district Grabag 1 Magelang. Methods. The Design of this study using cross sectional method. The sample used In This study were 35 respondents from a total population of 182 respondents drawn using formulas Lameshow. Normality test used is the Shapiro- Wilktest, and the results of data analysis used Spearman's test. Results. There was no association between stress in the third trimester pregnant women to the fetus activity with p= 0.000 (0.05). And test results obtained value of p = 0.778 ( 0.05), which means that Ho is accepted and Ha is rejectedRecommendation. to increase knowledge about stress in pregnant women and become learning materials for further research